The pressure-induced metallization of monoclinic vanadium dioxide. Issue 107 (3rd November 2016) - Zhang, Huafang; Li, Quanjun; Cheng, Benyuan; Guan, Zhou; Liu, Ran; Liu, Bo; Liu, Zhenxian; Li, Xiaodong; Cui, Tian; Liu, Bingbing
Abstract : The structure transition sequence follow M1 → M'1 → X, the PIM in M′1 phase occurs at 43.2 GPa and mainly driven by electron-correlation. Abstract : In this study, the high-pressure behavior of monoclinic vanadium dioxide (VO2 (M1 )) was revisited using infrared reflectivity (IR) spectroscopy, Raman spectroscopy and in situ synchrotron X-ray diffraction (XRD) up to 64.7 GPa. Upon compression, VO2 (M1 ) follows the expected the structure transition sequence, M1 → M′1 → X, and we found that the structural transition from M′1 to X phase is completed at about 59 GPa. Moreover, our IR data demonstrated that the M′1 phase is a semiconductor within the pressure region of 11.4–43.2 GPa and became metallic with further compression, and that the X phase is metallic. Further analysis suggests that the pressure-induced metallization (PIM) of the M′1 phase is associated with electron–electron correlations, while the PIM from the M′1 to the X phases is relate to structural phase transitions. These results provide further insight into the PIM of VO2 (M1 ).